Insurance-markets Equilibrium with Sequential Non-convex Private and Public-Sector Labor Supply - Aleksandar, Vasilev (Journal of Mathematical Economics and Finance; Vol 2 No 2 (2016): JMEF Volume II, Issue 2(3), Winter 2016, 2017)
This paper describes the lottery- and insurance-market equilibrium in an economy with non-convex private- and public-sector employment. In contrast to Vasilev 2017, 2015, the public-sector labor supply decision is a sequential one. This requires two separate insurance market to operate, one for private-sector work, and one for public-sector employment. In addition, given that the labor choice for private- and public-sector hours is made in succession, the insurance market for public emloy- ment needs to open once the other insurance market has closed. This segmentation and sequentiality of insurance markets operation is a new result in the literature and a direct consequence of the double non-convexity, and the sequential nature of the sectoral labor supply decision.